Phosphotyrosine Phosphatases in Cancer Diagnostic and Treatment - Tiscornia, Maria M.; Riera, Mario A.; Lorenzati, Maria A.; Zapata, Pedro D. (Recent Patents on DNA & Gene Sequences (Discontinued), 2010)
The activation of proteins by post-translational modification represents an important cellular mechanism for regulating most aspects of biological organization and control, including growth, development, homeostasis, and cellular communication. The complexity of protein modification includes phosphorylation and dephosphorylation, on proteins of different signaling pathways corresponding to growth, development, disease states, and aging. Current patents in phosphotyrosine phosphatases signaling pathway are focusing in diagnosis, prognosis and treatment. Many, new diagnosis techniques detect changes in mRNA expression with microarray technologies and others introduced specific antibodies for detection proteins changes, introducing to Biomedicine at Transcriptomic and Proteomic era. Many recent invent development alternative therapy with antibodies and inhibitors to PTPs that demonstrate the need to deepen understanding of the molecular mechanisms involved in the development of cancer.
Keywords: signaling pathway